1994
DOI: 10.1182/blood.v84.2.657.657
|View full text |Cite
|
Sign up to set email alerts
|

Long-term immunity to measles, mumps, and rubella after allogeneic bone marrow transplantation

Abstract: A total of 124 patients who had survived at least 2 years after allogeneic bone marrow transplantation (BMT) were studied. Serum was collected at least once yearly. IgG antibodies were determined by enzyme-linked immunosorbent assay for measles and mumps. Rubella antibodies were analyzed by radial hemolysis. Antibody levels were interpreted as representing immunity, seronegativity, or seropositivity, but with uncertain immunity. The median follow-up of the patients was 6.5 years (range, 2 to 13.5 years). The c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
51
1
1

Year Published

1997
1997
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 116 publications
(54 citation statements)
references
References 16 publications
1
51
1
1
Order By: Relevance
“…The corresponding probabilities were 37%, 12%, and 6% for mumps, and 47%, 33%, and 28% for rubella. They concluded that most allogeneic HSCT patients will become seronegative to nonlatent viruses during followup and long-term immunity, defined as persistent antibody not maintained regardless of the immune status of the donor [21]. However, since VZV is a latent and persistent virus, the time course of the disappearance of IgG after HSCT may be different from those of these nonlatent viruses.…”
Section: Discussionmentioning
confidence: 99%
“…The corresponding probabilities were 37%, 12%, and 6% for mumps, and 47%, 33%, and 28% for rubella. They concluded that most allogeneic HSCT patients will become seronegative to nonlatent viruses during followup and long-term immunity, defined as persistent antibody not maintained regardless of the immune status of the donor [21]. However, since VZV is a latent and persistent virus, the time course of the disappearance of IgG after HSCT may be different from those of these nonlatent viruses.…”
Section: Discussionmentioning
confidence: 99%
“…Ljungman et al [19] überprüften die Langzeitimmunität gegen Masern, Mumps und Röteln bei 57 Patienten nach allogener KMT. Von den zum Zeitpunkt der KMT seropositiven Patienten hatten 2 Jahre später 51 % noch Masern-AK, 42 % Mumps-AK, 76 % Röteln-AK.…”
Section: Immunologische Rekonstitution Und Impfschutz Nach Knochenmarunclassified
“…Following myeloablative allogeneic hematopoietic cell transplantation (HCT), full lymphocyte reconstitution and resolution of hypogammaglobulinemia may be protracted. 1,2 Human viral pathogens number in the hundreds, with thousands of possible strains, and clinically used proxies for risk of viral infection, such as absolute lymphocyte count (ALC) or total immunoglobulin levels (immunoglobulin G [IgG]), do not strongly predict protection against specific viral pathogens. Following HCT, preformed antibodies from the recipient continue to circulate, with an average halflife of ;26 days, and are thought to be slowly replaced by donor IgG following establishment of the donor B cell and plasma cell population much later.…”
Section: Introductionmentioning
confidence: 99%